ORIGINS, EVOLUTION, AND DIVERSIFICATION OF CLEPTOPARASITIC LINEAGES IN LONG‐TONGUED BEES. (7th June 2013) - Litman, Jessica R.; Praz, Christophe J.; Danforth, Bryan N.; Griswold, Terry L.; Cardinal, Sophie
<x xml:space="preserve">Abstract</x> The evolution of parasitic behavior may catalyze the exploitation of new ecological niches yet also binds the fate of a parasite to that of its host. It is thus not clear whether evolutionary transitions from free‐living organism to parasite lead to increased or decreased rates of diversification. We explore the evolution of brood parasitism in long‐tongued bees and find decreased rates of diversification in eight of 10 brood parasitic clades. We propose a pathway for the evolution of brood parasitic strategy and find that a strategy in which a closed host nest cell is parasitized and the host offspring is killed by the adult parasite represents an obligate first step in the appearance of a brood parasitic lineage; this ultimately evolves into a strategy in which an open host cell is parasitized and the host offspring is killed by a specialized larval instar. The transition to parasitizing open nest cells expanded the range of potential hosts for brood parasitic bees and played a fundamental role in the patterns of diversification seen in brood parasitic clades. We address the prevalence of brood parasitic lineages in certain families of bees and examine the evolution of brood parasitism in other groups of organisms.